Karakteristik Mutu Sirup Bit dengan Penambahan Carboxymethyl Cellulose - Pika Yulia Putri; Yusmarini Yusmarini; Dewi Fortuna Ayu (JURNAL AGROINDUSTRI HALAL, 2018)
This research aimed to study the influence of addition of carboxymethyl cellulose (CMC) and to get the best CMC concentration in making of beet syrup. The research was conducted with five treatments and three replications. The treatments in this study were CMC addition of 0.3%, 0.6%, 0.9%, 1.2%, and 1.5%. Data were statistically analyzed by using analysis of variance and followed by duncan new multiple range test at level 5%. The result of analysis of variance showed that the influence of CMC had significantly affected pH, total dissolved solid, sucrose level, and viscosity. The treatment also significantly effected aroma and hedonic test, but didn’t significantly affected colour and flavor of beet syrup. Based on this research, the best treatment was syrup with 0.9% CMC addition which had pH 5.75, total dissolved solids 71.16°brix, viscosity 351.56 cP, and sucrose level 69.68%. Characteristics of best treatment syrup based on descriptive test were red purple colour, beet root flavor, sweet taste, thick, and on hedonic test was favored by panelists.Keywords: Syrup, beet root, carboxymethyl cellulose (CMC)